"Beyond Bali": a transformative education approach for developing community resilience to violent extremism. Issue 2 (3rd April 2017) - Taylor, Elisabeth (Lily); Taylor, Peter Charles; Karnovsky, Saul; Aly, Anne; Taylor, Nell
Abstract: The Bali bombings of 2002 and 2005 confronted Australia and its neighbours directly for the first time with the dangers of violent extremism. Since then, the Bali Peace Park Association (BPPA), consisting of former victims, their families and other interested parties, has been lobbying for the creation of the "Bali Peace Park" to be built on one of the bombing sites. Peace parks have been conceived as community-driven projects against violent extremism, and the planned Bali Peace Park embodies this principle. In 2012, the BPPA initiated "Beyond Bali", an ambitious and highly relevant curriculum development project, and secured funding from the Australian Attorney General's Department. Drawing on the expertise of a counter-terrorism expert, two university education experts and the first-hand experiences of victims and their families, the Beyond Bali curriculum package was created. Beyond Bali covers a range of topics and activities, including social science studies and ethical dilemma learning, is suitable for Years 8 and 9 students studying the Australian Curriculum, and is available for free from the BPPA:http://www.balipeacepark.com.au/beyond-bali-education-package.html . In this paper we position Beyond Bali as a transformative education resource within the fields of peace and global education and argue that it embodies UNESCO's "learning to be" principle .